Identification and inventory of reef fish abundance in West Simeulue MPA, Aceh, Indonesia. Issue 1 (February 2021) - Ulfah, M; Isfani, R K; Indra; Turnip, I N; Dirgantara, R
Abstract: The marine protected area of the West Simeulu is one of the MPA that have been reserved by the Aceh Governor as a marine protacted areas in 2018. Identification and inventory of reef fish abundance in the MPA West Simeulue can be used as an initial reference to see the effectiveness of this area, so that it can give changes to the West Simeulue MPA. This research was conducted in October 2019 with 9 observation locations. The method used was the under water visual census (UVC) at 2 in depths (shallow and deep). It was found that as many as 30 families with 13.107 individuals from 163 species were found in the West Simeulue MPA with reef fish abundance values of 1.069 ind/ha in the MPA and 906 ind/ha outside the MPA. Pomacentridae and Acanthuridae were the families with the highest number of individuals found, with value of 5.550 and 2.226 individuals, respectively.